ASA, NSAIDs, Coxibs and Colorectal Cancer Prevention — How Far Have We Come?. (1st July 2004) - Fishman, Martin
Abstract : This paper described a nested case-control study on all Quebec patients over 65 years of age who underwent total colonic imaging or surgery for colorectal cancer (CRC) during a specified six-month period without similar testing in the preceding year. Information from the provincial government database was collected for each subject to estimate the consumption of prescription acetylsalicylic acid (ASA), standard nonsteroidal anti-inflammatory drugs (NSAIDs) and cyclooxygenase-2- specific inhibitors (coxibs) during the previous year. Of 2568 subjects, 730 were found to have at least one adenoma (but not carcinoma) and 129 were found to have CRC (with or without adenoma). Patients with and without adenoma or carcinoma were compared for type, amount and duration of drug exposure to determine if there was a protective effect. Rofecoxib and NSAIDs were associated with reduced incidence of colorectal adenoma (CRA), and these drugs and celecoxib protected against CRA and CRC.